Adoption of improved cassava varieties in Uganda: implications for agricultural research and technology dissemination - Abele, S.; Twine, Edgar E.; Ntawuruhunga, Pheneas; Baguma, Yona K.; Kanobe, C.; Bua, A. (2007)
Improved germplasm from the cassava-breeding program has generated new varieties that are increasingly being grown by farmers in Uganda.In this study, the socio-economic and demographic characteristics of cassava farmers in different regions of Uganda, adopted cassava varieties, their adoption rates, desirable and undesirable attributes, and factors that have influenced the speed of adoption of the most adopted variety were determined. The negative binomial model was used to analyze the determinants of the speed of adoption of the most widely adopted cassava variety. NASE 1, NASE 2, NASE 3, NASE 4, NASE 10 and NASE 12 are the varieties so far adopted. NASE 3 is the most widely adopted, to adoption levels as high as 77% in central Uganda. Farmers consider disease resistance, maturity period, taste, dry matter content, cyanide content, inground storability and diversity in forms of utilization in their decision to adopt new cassava varieties. From the Negative Binomial model, speed of adoption of NASE 3 was positively and significantly influenced by age of household head, household size and access to extension services. However, it was negatively and significantly influenced by number of hoes owned by a household. The considerable variability within the crop can be exploited to ensure that each variety has a fair blend of all desirable quality attributes. There is need to continue breeding for adaptability to biotic stresses such as diseases while improving on attributes that influence palatability and nutritive value of the crop. With respect to technology dissemination, strengthening the link between farmers and agricultural extension agents/service providers and improving the targeting of extension services will enhance the adoption of new cassava varieties.